Hedgehog Signaling Non-Canonical Activated by Pro-Inflammatory Cytokines in Pancreatic Ductal Adenocarcinoma - Wang, Yuqiong (J Cancer, 2016)
Hedgehog(HH) pathway is found to be activated through a manner of canonical, or the non-canonical HH pathways. Distinct hyperplasia stroma around tumor cells is supposed to express pro-inflammatory cytokines abundantly, such as tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β), etc. in pancreatic ductal adenocarcinoma (PDAC) tissues. In this study we observed the effects of TNF-α and IL-1β on HH pathway activation in PDAC cells, and explored their activation manners. Our results showed that pro-inflammatory cytokines, TNF-α and IL-1β, could up-regulate the expression of GLI1 gene, increase its nuclear protein expression and promote malignant cell behaviors including migration, invasion, epithelial-mesenchymal transition (EMT) and drug resistance as well. Moreover, GLI1 promoter-reporter assay in combination with blocking either NF-κB or Smoothened (SMO) suggested that TNF-α and IL-1β could transcriptionally up-regulate expression of GLI1 completely via NF-κB, whereas ablation of SMO could not completely attenuate the regulation effects of TNF-α and IL-1β on GLI1 expression. Collectively, our results indicated that TNF-α and IL-1β in hyperplasia stroma can promote the PDAC cell development by activating HH pathway, through both the canonical and non-canonical HH activation ways.